The Concept of the Estimation of Phase Diagrams (An Optimised Set of Simplified Equations to Estimate Equilibrium Liquidus and Solidus Temperatures, Partition Ratios, and Liquidus Slopes for Quick Access to Equilibrium Data in Solidification Software) Part I: Binary Equilibrium Phase Diagrams - Gergely Kőrösy; András Roósz; Tamás Mende (Metals)
This paper presents equations derived from thermodynamic equations for calculating the liquidus and solidus temperatures, the liquidus slope, and the partition ratio for solidification simulations. The constants of these equations can be easily determined from measurement data obtained by digitalisation from known diagrams or can be calculated using a CALPHAD-based software. ESTPHAD has a hierarchical system; the developed functions of the binary systems are used in the calculation of the functions of the ternary systems, the functions of the ternary systems in the calculation of the function of quaternary systems, and so on. The developed method is demonstrated by processing the liquidus and solidus of Si–Ge isomorphous and Al–Mg and Al–Si eutectic equilibrium phase diagrams. The use of this method for calculating the functions of ternary systems will be shown in Part II. The advantages of this method are that the equations are simple, can be determined very quickly, and can be built into the simulation software very easily. The most significant advantage is that the calculation time is shorter by some order of magnitude than that of a CALPHAD-type calculation.